Regional cancer therapy - Schlag, Peter M. (Cancer drug discovery and development)
Regional cancer therapies remain important options in the management of malignant disease, in spite of the venue of more targeted agents for systemic therapies. New tecnologies and better guidance systems for radiofrequency ablation and intrastitial laser therapies, highly selective intravascular approaches with improved catheters and guidance systems, improved agents for embolizations, and new vasoactive drugs for isolated limb and liver perfusions are just a few of the new developments in a field that is alive and progressing. Regional Cancer Therapy, so well put together by the editors Peter M. Schlag and Ulrike S. Stein, presents an overview of today’s realities and tomorrow’s possibilities. Regional cancer therapy models provide ways to make new discoveries about tumor biology and new agents that may be used regionally as well as systemically. This book should therefore be of interest to all clinicians and scientists with an interest in tumor biology as well as clinical advances. Alexander M. M. Eggermont, MD, PhD Professor and Head of Surgical Oncology Erasmus University MC—Daniel den Hoed Cancer Center Rotterdam, the Netherlands v PREFACE The treatment of malignant tumors has been substantially improved in recent years due to developments in clinical medicine and technology as well as by advances in mole- lar biological research. Modern molecular and genetic techniques allow the charact- ization of molecules that are decisive for tumor development and progression. Background - Biological background - Pharmacological background - Isolated limb and organ perfusion laboratory models - Techniques and prerequisites for regional therapy - Interventional radiotherapy - Surgical strategies - Regional thermotherapy - Radiofrequency thermal ablation - Cryoablation for primary and secondary liver tumors - A personal history of photodynamic therapy - Ultrasound-guided therapy - Nanocarriers and drug delivery - Local gene therapy for cancer - Indications and results for different tumor entities - Regional chemotherapy of primary and metastatic liver tumors - Focal liver ablation techniques in primary and secondary liver tumors - Regional therapy for peritoneal surface malignancy - Malignant peritoneal mesothelioma - Regional therapy of pancreatic cancer - Regional breast cancer treatment - Regional therapy in ovarian cancer - Regional therapy of bladder tumors - Regional therapy of rectal cancer - Percutaneous laser ablation of lung metastases - Regional therapy of brain tumors - Hyperthermic intrapleural chemotherapy in pleural malignancy - Isolated limb perfusion in advanced soft tissue sarcomas - Isolated limb perfusion for melanoma in transit metastases - Outpatient brachytherapy with seeds.